1982
DOI: 10.1007/bf01258247
|View full text |Cite
|
Sign up to set email alerts
|

Smooth endoplasmic reticulum and other agranular reticulum in frog retinal photoreceptors

Abstract: Frog retinal photoreceptors are favourable material for studying a number of unresolved issues concerning the interconnections, three-dimensional organization and functions of intracellular membrane systems in neurons. At least two distinct regions of smooth endoplasmic reticulum (SER) are present in these cells. One region, the subellipsoid SER, is located in rod cells at the base of the mitochondria-rich ellipsoid region, and is comprised of arrays of stacked tubules which exhibit frequent continuities with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 91 publications
9
55
1
Order By: Relevance
“…At higher confocal gains, SERCA2 immunofluorescence was observed in mouse photoreceptor inner segments (ISs; arrowheads in Fig. 1B), consistent with SERCA2 expression in the IS region that contains large amounts of ER cisternae (Mercurio and Holtzman, 1982). The most pronounced SERCA2 signal in mouse was detected in cell bodies of presumed amacrine cells lining the proximal end of the INL and in cells localized to the ganglion cell layer (arrows in Fig.…”
Section: Light Microscopic Localization Of Sercas In the Mammalian Rementioning
confidence: 65%
See 1 more Smart Citation
“…At higher confocal gains, SERCA2 immunofluorescence was observed in mouse photoreceptor inner segments (ISs; arrowheads in Fig. 1B), consistent with SERCA2 expression in the IS region that contains large amounts of ER cisternae (Mercurio and Holtzman, 1982). The most pronounced SERCA2 signal in mouse was detected in cell bodies of presumed amacrine cells lining the proximal end of the INL and in cells localized to the ganglion cell layer (arrows in Fig.…”
Section: Light Microscopic Localization Of Sercas In the Mammalian Rementioning
confidence: 65%
“…In neurons, the ER consists of a network of cisternae extending throughout the cell, from the synaptic terminal to dendritic branches (Mercurio and Holtzman, 1982;Verkhratsky, 2005). Ca 2+ release from and sequestration into neuronal ER can exert both local and global control over Ca 2+ -dependent cytoplasmic events, allowing it to regulate many cellular functions, including gene expression, protein synthesis, synaptic transmission and apoptosis (reviewed in Meldolesi and Pozzan, 2002;Berridge et al, 2003;Breckenridge et al, 2003;Verkhratsky, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…ER and its specializations are found in all parts of the inner segment, including the soma and the synaptic terminal (149)(150). Ca 2+ is sequestered into both rough and smooth ER (151)(152)(153).…”
Section: Intracellular Ca 2+ Stores In the Inner Segmentmentioning
confidence: 99%
“…The density of the ER structures is highest in the subellipsoid space (the myoid), from which other organelles are effectively excluded. The myoid ER is involved in synthesis of OS and IS proteins (149). It is thought to be continuous with the smooth ER which has access into synaptic terminals (149,151).…”
Section: Intracellular Ca 2+ Stores In the Inner Segmentmentioning
confidence: 99%
“…Intracellular calcium is stored and released from the endoplasmic reticulum. Ultrastructural studies revealed smooth endoplasmic reticulum in the inner segments and synaptic terminals of photoreceptors [154] capable of accumulating calcium ions [155]. There are two principal mechanisms of calcium release from internal stores: CICR mediated by ryanodine receptors and release mediated by receptors for the second messenger, IP3 [156].…”
Section: Intracellular Calcium Handlingmentioning
confidence: 99%